Remote ischaemic preconditioning of the lung: from bench to bedside—are we there yet? - Weber, Nina C.; Zuurbier, Coert J.; Hollmann, Markus W. (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Despite several decades of research on varying forms of “conditioning” different organs (heart, brain, kidney and lung), we have yet not discovered the therapeutic realisation of these potential powerful protective interventions. However, several experimental and also clinical studies have shown that conditioning an organ ultimately prevents ischaemic and reperfusion damage of that organ during clinical interventions.